An extremely rare case of ovarian abscess in third trimester of pregnancy managed by successful vaginal birth and review of literature - Vuong, Anh Dinh Bao; Nguyen, Phuc Nhon (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Ovarian abscess (OA) in pregnancy is actually rare occurrence, almost unheard, which associated with poor prognosis for mother and fetus. This diagnostic dilemma is often difficult to be elucidated because of anatomical changes in pregnancy. It was established incidentally by obstetric ultrasound or during cesarean section performed for an obstetric indication. Specially, the presentation of adnexal abscess is very hard to distinguish from appendical abscess. In this report, we presented a 20-year-old woman (G0P0) at 33-34 weeks of gestation was admitted to the clinic of our hospital with a pelvic abnormal tumour accompanied by fetal growth restriction. The patient was indicated for serial laboratory examination, which showed a right abnormal adnexal mass. At hospitalization, the patient was mostly asymptomatic so she was followed by medical treatment and by an expectant management. The surveillance was strictly controlled without complications, except intrauterine growth restriction associated with pregnancy. The patient received a conservative management and gave a well-being infant at 36-37 weeks of gestation by vaginal delivery. Twelfth days after delivery, she underwent a laparoscopic operation to remove the abscess mass. Preventive treatment is also a major importance. This report describes the clinical features and results of the case with an ovarian abscess detected in the 3rd trimester without adverse sequelae and compared to the recurrent knowledge based on the literature regarding the advanced management of OA involved in pregnancy. Through this report, we aim to carry out a literature review in order to discuss these clinical manifestations of OA, optimize the importance in definitive diagnosis and underline the appropriate treatment of an individual case.